Philosophy, Science, and History Ages Of The State And The Three-Stage Law Comparative (Damascus University Journal of arts and humanities sciences, 2021)
The research attempts to shed light on the most important ideas which were put forward by the two pioneers of contemporary sociology, namely; the Arab scholar and intellectual Mohammad bin Abdurrahman Ibn Khaldun, and the French philosopher Auguste comte); though a comparison between their ideas concerning science, philosophy, history, and the evolution of countries and societies. The research highlights the social and cultural background of each of scholars, and the effect of environment and culture on their own theories, namely; Ibn Khaldun’s Human civilization Theory, and The law of the Three Stages of Auguste Comte while indicating the time difference between them. The research has adopted the analytical approach, which enabled the use of the method of comparison between the statements of each of the two scholars.The research has concluded with results listed at the end of the research.
Keywords: Philosophy, Science, and History Ages Of The State And The Three-Stage Law Comparative